Rifaximin versus Nonabsorbable Disaccharides for the Treatment of Hepatic Encephalopathy: A Meta-Analysis - Dong Wu; Shu-Mei Wu; Jie Lu; Ying-Qun Zhou; Ling Xu; Chuan-Yong Guo (Gastroenterology Research and Practice)
Background. Many studies have found that the antibiotic rifaximin is effective for the treatment of hepatic encephalopathy. However, there is no uniform view on the efficacy and safety of rifaximin. Methods. We performed a meta-analysis through electronic searches to evaluate the efficacy and safety of rifaximin in comparison with nonabsorbable disaccharides. Results. A total of 8 randomized controlled trials including 407 patients were included. The efficacy of rifaximin was equivalent to nonabsorbable disaccharides according to the statistical data (risk ratio (RR): 1.06, 95% CI: 0.94–1.19; P=0.34). Analysis showed that patients treated with rifaximin had better results in serum ammonia levels (weighted mean difference (WMD): −10.63, 95% CI: −30.63–9.38; P=0.30), mental status (WMD: −0.32, 95% CI: −0.67–0.03; P=0.07), asterixis (WMD: −0.12, 95% CI: −0.31–0.08; P=0.23), electroencephalogram response (WMD: −0.21, 95% CI: −0.34–−0.09; P=0.0007), and grades of portosystemic encephalopathy (WMD: −2.30, 95% CI: −2.78–−1.82; P<0.00001), but only the last ones had statistical significance. The safety of rifaximin was better than nonabsorbable disaccharides (RR: 0.19, 95% CI: 0.10–0.34; P<0.00001). Conclusion. Rifaximin is at least as effective as nonabsorbable disaccharides, maybe better for the treatment of hepatic encephalopathy. And the safety of rifaximin is better.